The discourse of digital persuasion: unmasking Aristotelian rhetorical strategies in Harvard's EdX MOOCs - Ricahyono, Sigit (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2023)
This study looked into how Harvard University's EdX Massive Open Online Courses (MOOCs) strategically employed the Aristotelian rhetorical aspects of pathos, ethos, and logos to comprehend their digital persuasion methods. It employed content analysis to examine three MOOCs' "about this course" sections: "Rhetoric," "Ancient Masterpieces," and "Pyramids of Giza." After careful examination, the "Rhetoric" MOOC received an impressive high score of 8, indicating a strong dedication to academic rigor in the digital realm. Deliberately incorporating pathos (7) was found to be an effective strategy for emotionally engrossing learners in virtual environments across MOOCs. In addition, Harvard's excellent display of credibility, authority, and ethical appeal in the digital sphere was underlined by consistently high ethos scores (8 for "Rhetoric," 5 for "Ancient," and 6 for "Giza"). The study's findings highlight Harvard's deft application of digital persuasion techniques in EdX MOOCs, demonstrating the university's smooth transition of its prestigious reputation into the digital learning space while adjusting to the changing needs of education, especially in the AI-driven world of today.